2006
DOI: 10.1073/pnas.0506307103
|View full text |Cite
|
Sign up to set email alerts
|

New insights into myosin evolution and classification

Abstract: Myosins are eukaryotic actin-dependent molecular motors important for a broad range of functions like muscle contraction, vision, hearing, cell motility, and host cell invasion of apicomplexan parasites. Myosin heavy chains consist of distinct head, neck, and tail domains and have previously been categorized into 18 different classes based on phylogenetic analysis of their conserved heads. Here we describe a comprehensive phylogenetic examination of many previously unclassified myosins, with particular emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
442
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(454 citation statements)
references
References 49 publications
9
442
2
1
Order By: Relevance
“…Dictyostelium discoideum MyoM contains a Rac guaninenucleotide exchange factor domain that has a PH subdomain 134 and associates with macropinocytic structures 135 . Last, genome mining revealed a human myosin that contains a FYVE domain that is thought to interact with endosomal phosphatidylinositol-3-phosphate 136 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…Dictyostelium discoideum MyoM contains a Rac guaninenucleotide exchange factor domain that has a PH subdomain 134 and associates with macropinocytic structures 135 . Last, genome mining revealed a human myosin that contains a FYVE domain that is thought to interact with endosomal phosphatidylinositol-3-phosphate 136 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…Evolution of myosins involved a complex history of lineage-specific duplications, such that the myosin superfamily is subdivided into as many as 37 classes (Richards and Cavalier-Smith, 2005;Foth et al, 2006). The angiosperms have two classes of myosins, VIII and XI, with the latter being the largest.…”
mentioning
confidence: 99%
“…The T. gondii possesses the largest repertoire for each of the three types of motors found in any apicomplexan to date: 10 genes giving rise to at least 11 myosin heavy chains and 15 and 10 genes encode kinesin and dynein heavy chains, respectively. Phylogenetic analysis of the conserved head domains groups six T. gondii myosins into the alveolate-specific class XIV, two into the wellknown class VI, and one sequence each into the newly described myosin classes XXII, XXIII, and XXIV (Foth et al, 2006). We have showed that TgMyoD exhibits the same kinetics properties as TgMyoA but a conventional knockout has established that this motor does not play a significant role in motility of tachyzoites.…”
Section: Myosin Motorsmentioning
confidence: 89%
“…1). Our recent phylogenetic analysis of the repertoire of myosins in Apicomplexa and in others protozoans led us to postulate that other motors could potentially contribute to gliding motility (Foth et al, 2006) given the fact that T. gondii tachyzoites exhibit three distinct modes of motility (Hakansson et al, 1999). The T. gondii possesses the largest repertoire for each of the three types of motors found in any apicomplexan to date: 10 genes giving rise to at least 11 myosin heavy chains and 15 and 10 genes encode kinesin and dynein heavy chains, respectively.…”
Section: Myosin Motorsmentioning
confidence: 99%
See 1 more Smart Citation